Enhancing oil palm seedling growth through the utilization of guano in early nursery stage - Kautsar, Valensi; Afrizal; Parwati, Wiwin Dyah Ully (Fakultas Pertanian Universitas Yudharta Pasuruan, 2025)
Introduction: Oil palm nurseries are crucial to oil palm farming success. Thus, precise management measures from the start, such as giving nutrients and using optimal planting material, are essential. Vermicompost and guano were tested as organic fertilizers in oil palm fields to replace chemical fertilizers. This study aims to evaluate the effect of guano and vermicompost as organic fertilizers on the growth of oil palm seedlings during the pre-nursery stage. Methods: Besides the control group, the experimental treatments included 10% vermicompost, 20% vermicompost, 10% guano, and 20% guano, each replicated five times in a completely randomized design. Results: The introduction of 10% guano resulted in a significant enhancement across key growth metrics Addition of 10% guano had 20.0% more leaves, 22.5% more stem diameter, and 62.1% more shoot dry weight than the control group. This study shows that guano, which includes 19% P2O5, can boost oil palm seedling growth. The inceptisols was already rich in nutrients, thus vermicompost had no effect on it throughout the three-month testing. Since the soil conditions were good, vermicompost did not change them during the three-month trial. The correlation matrix showed a strong and constant link between seedling shoot and root fresh and dry weights. The relationship between organic fertilizers and oil palm nursery growth highlights the importance of a well-rounded plant development profile. This highlights the complex relationship between organic fertilizers and oil palm growth. Conclusion: Guano at 10% has been shown to improve oil palm seedling growth in the nursery phase, outperforming vermicompost.